2012
DOI: 10.1111/j.1365-2516.2012.02866.x
|View full text |Cite
|
Sign up to set email alerts
|

Experience of recombinant activated factor VII usage during surgery in patients with haemophilia with inhibitors

Abstract: Inhibitor development is one of the most challenging complications of haemophilia management. Haemostatic control in patients with haemophilia with inhibitors can be difficult, and is especially risky in those undergoing surgical interventions. Most haemophilia patients with inhibitors suffer from chronic joint disease requiring surgical correction due to recurrent bleeding episodes. The aim of this study was to assess the use of recombinant activated factor VII (rFVIIa) as haemostatic therapy during orthopaed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 16 publications
0
7
0
Order By: Relevance
“…Across all 35 publications, there was a wide range of surgical procedures categorized as being major or minor (Tables 1 and 2). 9,16 –42 Two articles defined surgical specialties (eg, orthopedic, cardiothoracic, neurosurgical), rather than individual procedures, as being major or minor. 18,40 In general, major surgical procedures were more likely to have been carried out under general anesthetic, while minor surgical procedures tended to be carried out under local anesthetic (Table 2).…”
Section: Resultsmentioning
confidence: 99%
“…Across all 35 publications, there was a wide range of surgical procedures categorized as being major or minor (Tables 1 and 2). 9,16 –42 Two articles defined surgical specialties (eg, orthopedic, cardiothoracic, neurosurgical), rather than individual procedures, as being major or minor. 18,40 In general, major surgical procedures were more likely to have been carried out under general anesthetic, while minor surgical procedures tended to be carried out under local anesthetic (Table 2).…”
Section: Resultsmentioning
confidence: 99%
“…Inhibitory antibodies to factor VIII (FVIII) or IX (FIX) are formed as notable complications in 10-30% and 2-5% of patients with hemophilia A and B, respectively [ 1 ]. This poses challenging problems for clinicians treating patients with hemophilia A or B undergoing surgical interventions in that inhibitors not only rapidly inactivate coagulation factordeficient concentrates but also stimulate the synthesis of new antibodies [ 2 ]. According to a recent European study [ 3 ], hemophilia patients with inhibitors are more vulnerable to arthropathy and orthopedic and musculoskeletal complications leading to a prolonged hospital stay and uncontrolled bleeding compared with those without inhibitors.…”
Section: Introductionmentioning
confidence: 99%
“…That is, prevention for bleeding should be considered during the perioperative period. Bypassing agents are used to control and prevent bleeding during the perioperative period in hemophilia patients with inhibitors [ 1 2 6 7 8 ]. Two types of bypassing agents are currently available in the clinical setting: activated prothrombin complex concentrates (APCC) (FEIB; Baxter, Vienna, Austria) and recombinant activated factor VII (rFVIIa) (NovoSeven; Novo Nordisk, Bagsvaerd, Denmark).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The use of rFVIIa in open surgery in a patient with haemophilia and inhibitors was first reported in 1988 . Subsequently, a prospective double‐blind randomised dose‐finding surgical trial comparing rFVIIa 35 μg/kg vs. 90 μg/kg , and a number of retrospective reports, has established the safety and efficacy of rFVIIa for EOS in patients with inhibitors . Overall, these reports showed that rFVIIa is efficacious in controlling haemostasis peri‐ and post‐operatively in patients with inhibitors in both major and minor surgical procedures (Table ).…”
Section: Haemostatic Therapy and Outcomes In Eosmentioning
confidence: 99%